Goal Directed Worry Rules Are Associated with Distinct Patterns of Amygdala Functional Connectivity and Vagal Modulation during Perseverative Cognition - Meeten, Frances; Davey, Graham C. L.; Makovac, Elena; Watson, David R.; Garfinkel, Sarah N.; Critchley, Hugo D.; Ottaviani, Cristina (Frontiers in Human Neuroscience, 2016)
Excessive and uncontrollable worry is a defining feature of Generalized Anxiety Disorder. An important endeavor in the treatment of pathological worry is to understand why some people are unable to stop worrying once they have started. Worry perseveration is associated with a tendency to deploy goal-directed worry rules (known as ‘as many as can’ worry rules; AMA). These require attention to the goal of the worry task and continuation of worry until the aims of the ‘worry bout’ are achieved. This study examined the association between the tendency to use AMA worry rules and neural and autonomic responses to a perseverative cognition induction. To differentiate processes underlying AMA worry rule use from trait worry, we also examined the relationship between scores on the Penn State Worry Questionnaire and neural and autonomic responses following the same induction. We used resting-state functional magnetic resonance brain imaging while measuring emotional bodily arousal from heart rate variability (where decreased HRV indicates stress-related parasympathetic withdrawal) in 19 patients with GAD and 21 control participants. Seed-based analyses were conducted to quantify brain changes in functional connectivity with the amygdala. The tendency to adopt an AMA worry rule was associated with validated measures of worry, anxiety, depression, and rumination. AMA worry rule endorsement predicted a stronger decrease in HRV and was positively associated with increased connectivity between right amygdala and locus coeruleus, a brainstem noradrenergic projection nucleus. Higher AMA scores were also associated with increased connectivity between amygdala and rostral superior frontal gyrus. Higher PSWQ scores amplified decreases in functional connectivity between right amygdala and subcallosal cortex, bilateral inferior frontal gyrus, middle frontal gyrus, and areas of parietal cortex. Our results identify neural mechanisms underlying the deployment of AMA worry rules. We propose that the relationship between AMA worry rules and increased connectivity between the amygdala and prefrontal cortex represents attempts by high worriers to maintain arousal and distress levels in order to feel prepared for future threats. Furthermore, we suggest that neural mechanisms associated with the PSWQ represent effortful inhibitory control during worry. These findings provide unique information about the neurobiological processes that underpin worry perseveration.